Epitafia dla romantyzmu polskiego na przełomie lat 80. i 90. XX wieku - Siatkowska-Callebat, Kinga (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The article is about three texts of Polish culture (a 1989 film by Tadeusz Konwicki, A Tale of Adam Mickiewicz’s ‘Forefathers’ Eve, based on Mickiewicz’s poem Dziady, and two novels: Rien ne va plus by Andrzej Bart, 1991 and List of the adulteresses. Travel prose by Jerzy Pilch, 1993) which seem to bid farewell to the long duration of Polish romanticism. The three works concur with Maria Janion’s thesis who heralded, in a democratic and independent Poland after the political changes of 1989, the twilight of the romantic paradigm as it had existed since the first half of the nineteenth century. A more detailed analysis of these cultural texts allows us to grasp the complexity and the ambiguity of the relationships that Konwicki, Bart and Pilch have with the romantic legacy.